Mexiletine rescues the mixed phenotype in SCN5A-1795insD hiPSC-CMs. (24th May 2021) - Nasilli, G; Yiangou, L; Palandri, C; Verkerk, AO; Davis, RP; Casini, S; Remme, CA
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The sodium channel blocker mexiletine can reduce late sodium current (INa) in patients with LQT3 syndrome, and additionally restore the decreased peak INa associated with SCN5A loss of function mutations. Purpose: To investigate whether mexiletinecan rescue the mixed phenotype associated with the SCN5A-1795insD mutation in human induced pluripotent stem cells derived cardiomyocytes (hiPSC-CMs). Methods and Results: HEK293 cells transfected with SCN5A-1795insD and SCN5A-WT and hiPSC-CMs from a patient carrying the SCN5A-1795insD mutation were incubated with a therapeutic dose of mexiletine (10 µM) or vehicle (H2O) for 48h. Peak INa, late INa and action potential (AP) properties were assessed by patch-clamp analysis. In HEK-293 cells transfected with SCN5A-1795insD or SCN5A-WT, exposure to mexiletine caused a significant increase in peak INa, in addition to a small increase in late INa in HEK-293 cells transfected with SCN5A-1795insD. In 1795insD hiPSC-CMs, peak INa was significantly increased whereas late INa was unchanged after mexiletine treatment. Accordingly, mexiletine increased AP upstroke velocity in SCN5A-1795insD hiPSC-CMs (indicating a rescue of INa availability), while AP amplitude, resting membrane potential and AP duration were unaffected. Conclusions: Chronic treatment with a therapeutic concentration of mexiletine is capable of rescuing the mixed phenotype in SCN5A-1795insD hiPSC-CMs.